Impact of SARS‐CoV‐2 infection on risk of prematurity, birthweight and obstetric complications: A multivariate analysis from a nationwide, population‐based retrospective cohort study. (15th April 2022) - Simon, Emmanuel; Gouyon, Jean‐Bernard; Cottenet, Jonathan; Bechraoui‐Quantin, Sonia; Rozenberg, Patrick; Mariet, Anne‐Sophie; Quantin, Catherine
Abstract: Objective: To determine the impact of maternal coronavirus disease 2019 (COVID‐19) on prematurity, birthweight and obstetric complications. Design: Nationwide, population‐based retrospective cohort study. Setting: National Programme de Médicalisation des Systèmes d'Information database in France. Population: All single births from March to December 2020: 510 387 deliveries, including 2927 (0.6%) with confirmed COVID‐19 in the mother and/or the newborn. Methods: The group with COVID‐19 was compared with the group without COVID‐19 using the chi‐square test or Fisher's exact test, and the Student's t test or Mann–Whitney U test. Logistic regressions were used to study the effect of COVID‐19 on the risk of prematurity or macrosomia (birthweight ≥4500 g). Main outcome measures: Prematurity less than 37, less than 28, 28–31, or 32–36 weeks of gestation; birthweight; obstetric complications. Results: In singleton pregnancies, COVID‐19 was associated with obstetric complications such as hypertension (2.8% versus 2.0%, p  < 0.01), pre‐eclampsia (3.6% versus 2.0%, p  < 0.01), diabetes (18.8% versus 14.4%, p  < 0.01) and caesarean delivery (26.8% versus 19.7%, p  < 0.01). Among pregnant women with COVID‐19, there was more prematurity between 28 and 31 weeks of gestation (1.3% versus 0.6%, p  < 0.01) and between 32 and 36 weeks of gestation (7.7% versus 4.3%, p  < 0.01), and more macrosomia (1.0% versus 0.7%, p = 0.04), but there was no difference in small‐for‐gestational‐age newborns (6.3% versus 8.7%, p  = 0.15). Logistic regression analysis for prematurity showed an adjusted odds ratio (aOR) of 1.77 (95% CI 1.55–2.01) for COVID‐19. For macrosomia, COVID‐19 resulted in non‐significant aOR of 1.38 (95% CI 0.95–2.00). Conclusions: COVID‐19 is a risk factor for prematurity, even after adjustment for other risk factors. Tweetable Abstract: The risk of prematurity is twice as high in women with COVID‐19 after adjustment for factors usually associated with prematurity. Tweetable Abstract: The risk of prematurity is twice as high in women with COVID‐19 after adjustment for factors usually associated with prematurity.